ASN, OTDA, POLITIK PILKADA SERENTAK DAN KORUPSI DI INDONESIA - Herdi Salioso (SISI LAIN REALITA, 2016)
Corruption is not a new term in Indonesia, only recently started realizing ingrained and entrenched. The problem of corruption becomes increasingly macro and massive when regional autonomy (OTDA) and coloring Election Political Democratization in Indonesia. The phenomenon of corruption which delivers Indonesia as the most corrupt country in the world, increasingly gives the impression assured in order to prevent and overcome, when the instrument and the substance of the existing law is not able to give effect deterrence for perpetrators and potential perpetrators.